Early marriage, education and mental health: experiences of adolescent girls in Mozambique - Nhampoca, Joaquim M.; Maritz, Jeanette E. (Frontiers in Global Women's Health, 2024)
Early marriage and maternity represent a violation of human rights and a barrier to achieving gender equality in education. Studies conducted across various regions and countries, including Mozambique, have highlighted the negative consequences of early marriage and maternity, particularly on adolescent girls' physical, educational and mental health. Adolescent girls who marry before the age of 18 are more prone to a broad spectrum of mood, anxiety, and other psychiatric disorders. In the districts of Maganja da Costa and Morrumbala in Zambézia Province, Mozambique, high rates of early marriage persist despite government policies and interventions.